THREADFIN BREAM (NEMIPTERUS) RESOURCES ALONG THE KERALA COAST WITH NOTES ON BIOLOGY OF NEMIPTERUS JAPONIC US - Vinci, G K (Indian Journal of Fisheries, 2011)
Nemtpterids are a group of quantitatively imporlEnl fsh alcng the Kerala coast.The greater concentratioi) of Nemipterush in 30-50m depth and the peak landingis in September. This is a carnivorous fish and feeding does not cease duringspawning season. N. Japonicus attains a length of 136 mm at the end of 1 year,186 mm at the end of II year and 236 mm at the end of HI year.